2005
DOI: 10.1159/000087725
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Aging: A More than Superficial Resemblance to Apoptosis?

Abstract: In physiological circumstances, erythrocyte aging leads to binding of autologous IgG followed by recognition and removal through phagocytosis, mainly by Kupffer cells in the liver. This process is triggered by the appearance of a senescent erythrocyte-specific antigen. The functional and structural characteristics of senescent erythrocytes strongly suggest that this antigen originates on band 3, probably by calcium-induced proteolysis. Generation of vesicles enriched in denatured hemoglobin is an integral part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
152
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(159 citation statements)
references
References 38 publications
(39 reference statements)
3
152
0
4
Order By: Relevance
“…An examination of erythrocyte size by FACS showed that the heterogeneity of erythrocyte sizes increased during aging in SOD1 −/− mice and that the average sizes were larger than those in SOD1 +/+ mice (Figure 1B). Since enlargement is a characteristic of aged erythrocytes that are efficiently trapped by the reticuloendothelial system followed by destructive elimination [28], these data suggest that the accelerated destruction of erythrocytes is the cause of the anaemia. In contrast with erythrocytes, the blood levels of reticulocytes ( Figure 1C) as well as platelets (results not shown) were significantly high and were increased with aging.…”
Section: Anaemic Phenotype Of Sod1-deficient Micementioning
confidence: 92%
“…An examination of erythrocyte size by FACS showed that the heterogeneity of erythrocyte sizes increased during aging in SOD1 −/− mice and that the average sizes were larger than those in SOD1 +/+ mice (Figure 1B). Since enlargement is a characteristic of aged erythrocytes that are efficiently trapped by the reticuloendothelial system followed by destructive elimination [28], these data suggest that the accelerated destruction of erythrocytes is the cause of the anaemia. In contrast with erythrocytes, the blood levels of reticulocytes ( Figure 1C) as well as platelets (results not shown) were significantly high and were increased with aging.…”
Section: Anaemic Phenotype Of Sod1-deficient Micementioning
confidence: 92%
“…The life span of erythrocytes amounts to some 100-120 days, that is, each day more than 200 billion erythrocytes need to be replaced, containing almost 20 mL of packed cell volume. Erythrocytes are considered to undergo senescence eventually resulting in the clearance of aged erythrocytes (1)(2)(3). Beyond that, erythrocytes are, similar to nucleated cells, cleared by suicidal death.…”
Section: Introductionmentioning
confidence: 99%
“…These include oxidation of band 3, leading to naturally occurring antibody-mediated opsonization followed by Fc-receptor mediated phagocytosis, and programmed or suicidal cell death. [1][2][3] Because RBC lack a nucleus and mitochondria, they do not undergo 'classic' apoptosis. However, features of programmed cell death have also been proposed for RBC ('eryptosis').…”
Section: Introductionmentioning
confidence: 99%